Associations between hedonic hunger and BMI during a two-year behavioural weight loss trial. - Mead, BR; Boyland, EJ; Christiansen, P; Halford, JCG; Jebb, S; Ahern, AL (Public Library of Science, 2021)
Objective: Prospective studies on relationships between hedonic hunger and BMI (Body Mass Index) during weight management are lacking. This study examined if hedonic hunger reduced during a behavioural weight management programme, and if hedonic hunger predicted future BMI.